Nursing Care for Spontaneous Head-Back Postpartum Patients in Hospital - Lukita, Yenni; M, Warda; Sallo, Andi Kamal M.; Nukuhaly, Hasnawati; Achmad, Ismiyanti H.; Kristina, Yunita (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Normal labor and birth is the process of expelling a fetus that occurs at term pregnancy (37-42 weeks), spontaneous birth with a posterior presentation, without complications for either the mother or fetus. The aim of the research is to be able to provide and implement nursing care for mothers with spontaneous post partum back of the head at Barru Hospital. The research method used was a case study method where the sample used was 1 respondent diagnosed with a mother with postpartum spontaneous back. The results of Spontaneous Post Partum Nursing Care for the Back of the Head at Barru Hospital found 2 nursing problems, namely Acute Pain and Risk of Infection. Providing nursing care lasts 2 x 24 hours. The conclusion is that the problem of post partum spontaneous back of the head nursing in hospitals can be resolved.